Testing Global ISM Models: A Detailed Comparison of O VI Column Densities with FUSE and Copernicus Data - de Avillez, Miguel (2012)
We study the O vi distribution in space and time in a representative section of the Galactic disk using three-dimensional adaptive mesh refinement hydrodynamic and magnetohydrodynamic simulations of the interstellar medium (ISM), including the disk-halo-disk circulation. The simulations describe a supernova-driven ISM on large (∼10 kpc) and small (∼1.25 pc) scales over a sufficiently large timescale (∼400 Myr) in order to establish a global dynamical equilibrium. The O vi column density, N(O vi), is monitored through line-of-sight measurements at different locations in the simulated disk. One has been deliberately chosen to be inside of a hot bubble, like our own Local Bubble, while the other locations are random. We obtain a correlation between N(O vi) and distance, which is independent of the observer’s vantage point in the disk. In particular, the location of the observer inside a hot bubble does not have any influence on the correlation, because the contribution of an individual bubble (with a typical extension of 100 pc) is negligibly small. We find a remarkable agreement between the O vi column densities (as a function of distance) and the averaged O vi density (∼1.8x10^-8 cm^-3) in the disk from our simulations and from the values observed with Copernicus and FUSE. Our results strongly support the important role of turbulent mixing in the distribution of O vi clumps in the ISM. Supernova-induced turbulence is quite strong and unavoidable due to shearing motions in the ISM, and it operates on a large range of scales.